Character education with live-in activities (Case study at De Britto College High School Yogyakarta) - Wulandari, Taat; Jayanti, Feri Dwi; Yacoob, Norazlan Hadi (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
The research aims to explain character education at De Britto College High School Yogyakarta. This school has unique characteristics in shaping the character of students. The unique thing about character education at this school is through live-in activities. This type of research is qualitative research. The research approach chosen is naturalistic. The research subjects were: principals, teachers and students at De Britto College High School Yogyakarta. Data collection techniques include: observation, interviews, and documentation. Data validity uses triangulation of data collection techniques. Data analysis uses the Miles and Huberman interactive model. The results of the research show that to shape the character of students, live-in activities are carried out in daily life. The character formation of students is carried out through educational excursions, live ins, and retreats or spiritual retreats. The organization of character education at De Britto College High School goes through 3 main stages, namely: educational excursion for class X, live-in for class XI, and retreat or spiritual practice for class XII. Implementing live-in activities sometimes has problems, including the limited number of teachers, the condition of students, such as the health of students when carrying out live-in activities.